Forecasting demand for frozen whole blocks of swanggi fish at PT. Hatni using a comparison of winter and decomposition methods - Muslimah, Tsaqofi Bintang; Hidayat, Hidayat; Negoro, Yanuar Pandu (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
PT. HATNI specializes in the export of frozen fish, particularly Swanggi (Priacanthus tayenus) and Kuniran fish. This study focuses on Swanggi fish due to its higher demand in the export market. Swanggi fish, a species of ray-finned marine fish, is characterized by blackish spots, large eyes, and a pink coloration, belonging to the family Priacanthidae. The objective of this research is to identify an effective forecasting method for estimating future export demand for frozen whole Swanggi fish, enabling the company to optimize its production and supply chain planning. Using 2023 data with evident seasonal patterns, trends, and seasonality, the study compares the Winter Multiplicative method and the Decomposition method. Through trial and error, the Winter Multiplicative method was identified as the most accurate, with parameters of α = 0.9, β = 0.1, and γ = 0.9. This method yielded the lowest error values: MAD of 1,602, MSD of 9,161,073, and MAPE of 3%. These results provide PT. HATNI with a reliable forecasting tool to meet future market demand effectively.